Customer engagement with brands in social media platforms: Configurations, equifinality and sharing. (9th September 2019) - Carlson, Jamie; Gudergan, Siegfried P.; Gelhard, Carsten; Rahman, Mohammad Mahfuzur
Abstract : Purpose: Social media brand platforms have become a popular means for engaged customers to share information and experiences with brands and other customers. However, empirical research on how customer engagement (CE) relates to customers' sharing intentions with the brand is limited. This study aims to investigate causal patterns of four CE dimensions – focused attention, absorption, enthusiasm and interaction – together with two cognitive structure properties in stimulating sharing intentions with the brand. Design/methodology/approach: Using data from 782 Chinese customers of brand pages on the social media platform Weibo, this paper is the first to use both finite mixture partial least squares (FIMIX-PLS) analysis and fuzzy-set qualitative comparative analysis (fsQCA) to empirically assess the impact of CE configurations on sharing intentions. Findings: The findings imply that not all of the CE dimensions co-occur necessarily and that different configurations of them can produce superior sharing intentions, conditional on the cognitive structure of customers, including their level of brand knowledge and avant-gardism. Research limitations/implications: Although restricted to customers on Weibo, the results inform practice about how social media technology can facilitate different CE configurations and customer sharing intentions. Practical implications: The results inform brand managers' segmentation efforts and CE content marketing initiatives that can induce different CE configurations and customer sharing intentions with customers that possess high avant-gard and brand knowledge characteristics. Originality/value: This study is the first to substantiate how different CE configurations (as gestalts) affect sharing intentions in social media and to challenge conventional net-effects thinking about CE dimensions. Understanding how such conditional configurations foster sharing via a social media platform is advantageous because it can improve segmentation efforts to strengthen brand relationships.